Nivel de conocimiento de la madre sobre tamizaje metabólico neonatal en el servicio de alojamiento conjunto del Hospital Iquitos “César Garayar García”, enero–diciembre 2024 - Mundaca Vidarte, Franshesca Katherina (2025)
Objectives: To determine mothers' level of knowledge about neonatal metabolic screening in the rooming-in service of the César Garayar García Hospital in Iquitos during 2024, and to identify its relationship with sociodemographic and obstetric characteristics. Methodology: This was a quantitative study with a non-experimental, descriptive, and cross-sectional design. The population consisted of postpartum mothers treated in the rooming-in service, who were administered a previously validated structured questionnaire. Results: A significant proportion of mothers are expected to have a low level of knowledge about neonatal screening, especially regarding its purpose and the diseases detected by this test, while knowledge about the procedure could be relatively higher. Furthermore, factors such as maternal age, educational level, parity, and counseling received are likely to significantly influence this level of knowledge. Conclusions: The expected findings will demonstrate the need to strengthen educational strategies and counseling in perinatal health, in order to promote greater informed participation of mothers in neonatal screening programs.